Have BMI an Impact in Short- and Long-Term Outcome After Pancreaticoduodenectomies? - Del Chiaro, Marco; Rangelova, Elena; Ansorge, Christoph; Blomberg, John; Segersvärd, Ralf (JOP. Journal of the Pancreas, 2012)
Context Increased BMI is generally considered a risk factor for postoperative complications after pancreaticoduodenectomy (PD). In contrast, data are scarce regarding BMI as long term prognostic factor. Objective To evaluate the impact of BMI on short and long term results after PD. Methods Patients undergone PD 2004-2010 was retrieved from our prospective database. Demographics, peri-operative data, morbidity, mortality, pancreatic fistula (PF) rate, length of stay (LOS), and survival were analyzed. The cohort was divided by BMI into overweight/obese (O; BMI ≥ 25 kg/m2) and controls (C; BMI <25 kg/m2). Results A total of 367 PDs were included (O=141/C=226). No significant differences were found between O and C regarding demographics, peri-operative data, morbidity (O 47% vs. C 54%) or mortality (O 3.4% vs. C 3.5%). O had a significantly higher rate of PF (O 20% vs. C 9.5%; P=0.006) and longer LOS (O 18 days vs. C 15 days; P=0.05) compared to C. An increasing risk for PF was observed with increasing BMI: underweight 0%, normal-weight 10%, overweight 16%, and obese 32% PF rate, respectively. A similar 1-, 3- and 5-year survival rate was observed for O and C both in pancreatic ductal adenocarcinoma, and in other periampullary cancers. Conclusion Overweight/obesity increases the risk for PF and thus LOS, but do not otherwise alter short term outcome or survival rate after oncological PD for pancreatic or periampullary cancer.